PENGARUH PENERAPAN METODE MIND MAPPING TERHADAP HASIL BELAJAR AKUNTANSI - Veri Aryanto Sopiansah; Leni Maryani (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
This study aims to determine the effect of applying the mind mapping method to learning outcomes in accounting. The research method used is the experimental method. Data collection techniques from this study included participant observation and learning achievement tests. The population in this study were class X students of the Accounting Study Program at Setia Bhakti Vocational High School, Bandung, totaling 54 students with a sample of all students. The results of this study indicate that there are differences in learning outcomes between the experimental group and learning that applies Mind Mapping and the control group with learning without applying Mind Mapping to accounting learning outcomes. The difference obtained is proven by testing the t-test hypothesis with the results tcount > ttable, where tcount is 2.134 and table is 1.68195. The implication of the results of this study is that teachers should apply the Mind Mapping learning method in teaching and learning activities in class, because the learning outcomes of Accounting applying Mind Mapping are better than without applying Mind Mapping.